MONITORING OF PHYSICAL EDUCATION CLASSES IN HYPERTHERMIC CONDITIONS (Scientific journal of the Fergana State University, 2023)
The article presents the results of a pedagogical experiment with schoolchildren in conditions of hyperthermia. The high efficiency of the inclusion in the training process of a complex of gymnastic exercises taken from the yoga system and the use of supercooling pauses is shown.It can be concluded that the inclusion in the training program of specially selected physical exercises of sufficiently high intensity and volume leads to an increase in energy costs (volleyball, basketball and national outdoor games) and leads to stabilization of body weight by equalizing the energy consumption of the body with energy consumption.The combination of static physical exercises aimed at developing physical abilities, such as flexibility, combined with the inclusion of sports and national outdoor games in the training process, has the greatest impact compared to traditional physical education classes.